The expertise variable associated with success in construction (Gaceta Técnica, 2023)
The development of this research had the objective of obtaining a mathematical model called La Pitia that addresses the management capacity of construction companies so that they can respond: Why are the delivery dates of the works not being met? Why is the quality pre-established in the regulations not being met? Why is industrial safety not complied with? Why are they exceeding planned costs? Why does construction management become a factor that generates pathologies? It is part of a job in the area of ​​construction prognosis, whose scope is to predict success. In this search, functions were obtained that model the company's ability to reduce the risks that it will face during the execution process, which have been called Expertise, which indicates how far or close it could be to the desired success in the execution of the work. The vast majority of construction companies in Venezuela do not receive feedback on the results obtained from their works, nor do they have a formal data arrangement system that allows reliable forecasts to be made, which is why the mathematical development of this work was based on concepts of Approximate Reasoning and Fuzzy Logic
Keywords: S Curve; Lessons Learned; La Pitia; Approximate Reasoning; Fuzzy Logic